2014
DOI: 10.1007/s10071-014-0783-7
|View full text |Cite
|
Sign up to set email alerts
|

Do tufted capuchin monkeys play the odds? Flexible risk preferences in Sapajus spp.

Abstract: As humans, several non-human animal species avoid risk, defined as "variability in rate of gain". However, non-human primate studies revealed a more complicated picture, with different species ranging from risk aversion to risk proneness. Within an ecological rationality framework, a species' feeding ecology should influence its risk preferences, as it has been shown in bonobos and chimpanzees. Although the feeding ecology hypothesis is promising, it has not been yet verified in species other than apes. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 51 publications
1
54
0
Order By: Relevance
“…In natural foraging contexts, individuals are required to take into account various different aspects simultaneously when making profitable decisions, such as whether to travel further afield for higher quality foods and how they can access extractable foods, for instance, through the use of tools. Such decisions may therefore be influenced by work-effort sensitivity, the level of perceived risk, attention to the functionality of available tools, and the quality of food available [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In natural foraging contexts, individuals are required to take into account various different aspects simultaneously when making profitable decisions, such as whether to travel further afield for higher quality foods and how they can access extractable foods, for instance, through the use of tools. Such decisions may therefore be influenced by work-effort sensitivity, the level of perceived risk, attention to the functionality of available tools, and the quality of food available [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the monkeys generally displayed risk-prone choices, but this preference could be overcome if the risky option delivered a relatively poor payoff. Similarly, capuchin monkeys also demonstrated a bias towards a risky option over a safe option and demonstrated near indifference between a suboptimal risky option and a safe option in one condition (De Petrillo, Ventricelli, Ponsi, & Addessi, 2015). …”
mentioning
confidence: 99%
“…We therefore wondered whether the same gap would be observed in nonhuman animals. Prior studies have found that, while general risk preferences may vary considerably across species (Bateson & Kacelnik, 1996;De Petrillo, Ventricelli, Ponsi, & Addessi, 2015;Heilbronner, Hayden, & Platt, 2009;Heilbronner, Rosati, Stevens, Hare, & Hauser, 2008), many of the fundamental decision-making biases found in humans can be replicated in nonhuman animals. For example, nonhuman primates, like humans, are ambiguity-averse (Hayden, Heilbronner, & Platt, 2010;Rosati & Hare, 2011) and are susceptible to loss versus gain framing effects (Chen, Lakshminarayanan, & Santos, 2006;Krupenye et al, 2015).…”
Section: Introductionmentioning
confidence: 99%